The Wnt non-canonical signaling modulates cabazitaxel sensitivity in prostate cancer cells - Sennoune, Souad R. (PLoS One, 2020)
BACKGROUND: Despite new drugs, metastatic prostate cancer remains fatal. Growing interest in the latest approved cabazitaxel taxane drug has markedly increased due to the survival benefits conferred when used at an earlier stage of the disease, its promising new therapeutic combination and formulation, and its differential toxicity. Still cabazitaxel’s mechanisms of resistance are poorly characterized. The goal of this study was thus to generate a new model of acquired resistance against cabazitaxel in order to unravel cabazitaxel’s resistance mechanisms. METHODS: Du145 cells were cultured with increasing concentrations of cabazitaxel, docetaxel/ taxane control or placebo/age-matched control. Once resistance was reached, Epithelial-to-Mesenchymal Translation (EMT) was tested by cell morphology, cell migration, and E/M markers expression profile. Cell transcriptomics were determined by RNA sequencing; related pathways were identified using IPA, PANTHER or KEGG software. The Wnt pathway was analyzed by western blotting, pharmacological and knock-down studies. RESULTS: While age-matched Du145 cells were sensitive to both taxane drugs, docetaxel-resistant cells were only resistant to docetaxel and cabazitaxel-resistant cells showed a partial cross-resistance to both drugs concomitant to EMT. Using RNA-sequencing, the Wnt non-canonical pathway was identified as exclusively activated in cabazitaxel resistant cells while the Wnt canonical pathway was restricted to docetaxel-resistant cells. Cabazitaxel-resistant cells showed a minimal crossover in the Wnt-pathway-related genes linked to docetaxel resistance validating our unique model of acquired resistance to cabazitaxel. Pharmacological and western blot studies confirmed these findings and suggest the implication of the Tyrosine kinase Ror2 receptor in cabazitaxel resistant cells. Variation in Ror2 expression level altered the sensitivity of prostate cancer cells to both drugs identifying a possible new target for taxane resistance. CONCLUSION: Our study represents the first demonstration that while Wnt pathway seems to play an important role in taxanes resistance, Wnt effectors responsible for taxane specificity remain un-identified prompting the need for more studies.